Stress and ways of dealing with stress in the work of professionally active teachers - Janiszewska, Mariola; Firlej, Ewelina; Drop, Bartłomiej; Barańska, Agnieszka; Ślusarska, Anna; Zabłocka, Ewa (Journal of Education, Health and Sport, 2018)
Introduction. Stress is an inherent part of human life. It is well known and often associated with negative professional or family situations. Stress is not dangerous to our body, but it reacts to it. Aim of work. The aim of the study was to investigate the stressors of professionally working teachers. Material and methods. The research was conducted from November 2016 to May 2017 among teachers working in primary schools in the Lubelskie Voivodship. The study covered 77 respondents. The diagnostic survey was used in the study, which was carried out through a self-report questionnaire. Calculations were made using Microsoft Office Excel 2010. Results. Researchers believe that the best way to cope with stress is to talk to loved ones (57%) and practice sports (39%). The respondents reported that they had neglected social interaction (25%) and had no leisure time for themselves and their family (44%). In the opinion of the respondents the greatest source of stress is noise (60%), which is most often encountered in the corridor during intercourse breaks. The most frequently reported symptom of somatic symptoms was headache (45%). The respondents do not see the possibility of promotion (44%) and some respondents want to improve their qualifications (34%) only to be able to stay in their position. Conclusions. Teachers should have clearly defined roles, less stressed, have optimized tasks, a sense of safety, a good work atmosphere, regular and objective assessments, and specific career paths that can eliminate stressful situations in the teaching profession.